On the appearance of fractional operators in non-linear stress–strain relation of metals. (October 2018) - Pinnola, F.P.; Zavarise, G.; Del Prete, A.; Franchi, R.
Abstract: Finding an accurate stress–strain relation, able to describe the mechanical behavior of metals during forming and machining processes, is an important challenge in several fields of mechanics, with significant repercussions in the technological field. Indeed, in order to predict the real mechanical behavior of materials, constitutive laws must be able to take into account elastic, viscous and plastic phenomena. Most constitutive models are based on empirical evidence and/or theoretical approaches, and provide a good prediction of the mechanical behavior of several materials. Here we present a non linear stress–strain relation based on fractional operators. The proposed constitutive law is based on integral formulation, and takes into account the viscoelastic behavior of the material and the inelastic phenomenon that appears when the stress reaches a particular yielding value. A specific case of the proposed constitutive law for imposed strain history is used to fit experimental data obtained from tensile tests on two kind of metal alloys. A best-fitting procedure demonstrates the accuracy of the proposed stress–strain relation and its results are compared to those obtained with some classical models. We conclude that the proposed model provides the best results in predicting the mechanical behavior for low and high values of stress/strain. Highlights: Stress–strain relation able to model mechanical behavior of metals is presented. Viscoelastic and inelastic phenomena are taken into account. Proposed model is based on integral formulation with time power-law kernels. Fractional operators appear in some particular cases. Evaluation of mechanical parameters by best fitting of experimental data.